Clinical Efficacy Observation of Acupuncture Treatment for Nonarteritic Anterior Ischemic Optic Neuropathy. (24th May 2015) - Qin, Yali; Yuan, Wei; Deng, Hui; Xiang, Zhanmei; Yang, Chao; Kou, Xinyun; Yang, Shufei; Wang, Zhijun; Jin, Ming
Abstract : Objective . To determine whether acupuncture treatment impacts the clinical efficacy of degenerative damage of the optic nerve caused by nonarteritic anterior ischemic optic neuropathy (NAION). Methods . 69 patients (93 eyes) with NAION who had been treated by acupuncture which is performed on different acupoints related to eyes by vertical insertion or Fingernail-pressure needle insertion. The best corrected visual acuity, mean defect (MD) and mean light sensitivity (MS) of the visual field, and latency and amplitude of pattern visual evoked potential (P-VEP) were compared before and after treatment. Results . After 2, 4, and 8 weeks of treatment, the total effective rates of visual acuity improvement were 74.19%, 78.89%, and 81.71%, respectively, and the decreased MD and increased MS were both statistically significant ( P < 0.01). When compared with the situation before treatment, the average latency of the P100 wave was significantly reduced ( P < 0.05), and the average amplitude was improved with no statistically significant difference ( P > 0.05). Conclusions . Acupuncture treatment could obviously improve the visual function of patients with NAION and be used as complementary and alternative therapy in clinic.